A proactive remote pharmaceutical care for rural elderly population: The Houston‐Apollo polypharmacy project. Issue 10 (1st July 2021) - Wang, Chen‐Yu; Chang, Kai‐Chieh; Chuang, Chin‐Ju; Chen, Yi‐Pin; Hsieh, Cheng‐Ying; Huang, Yung‐Cheng; Chen, Li‐Yu; Yang, Yi‐Hsuan; Jeng, Yachung; Chen, Hsiu‐Hsi; Liao, Ling‐Chiao; Liou, Horng‐Huei
Abstract: Aims: To evaluate polypharmacy‐related problems in the elderly people who live in rural through a proactive pharmaceutical care project under a novel remote medical service infrastructure (the Houston‐Apollo polypharmacy project). Methods: It is a prospectively cross‐sectional study. The elderly aged 65 years old lived in communities executed the congregate meal service and joined the Houston‐Apollo project were included. During March and July on 2020, the pharmaceutical care team of Houston‐Apollo polypharmacy project interviewed old people and collected their medications by remote video. Polypharmacy situation and drug‐related problems, including potentially inappropriate medications (PIMs), anticholinergic burden (ACB) and risk of sarcopaenia, were evaluated by clinical pharmacists. In addition, we analysed the categories of the prescription types between polypharmacy and non‐polypharmacy users, polypharmacy users with and without PIMs or ACB. A patient‐specific integrated pharmacist's note for medication education and a dear doctor letter (as needed) were generated and delivered within 2‐weeks postinterviewed. Age‐ and sex‐adjusted logistic regression model was used to evaluate the association between polypharmacy and these potential medication problems. Results: There were 87 older people (mean age = 75.9) and 536 long‐term medications were collected. Among them, 52% were defined as polypharmacy users. Polypharmacy was significantly associated with higher risk of PIMs and ACB. The adjusted odd ratio was 5.31 (95% CI: 2.02‐13.9) and 10.1 (95% CI: 3.4‐29.7), respectively. Among polypharmacy users, there were nearly double the prescriptions for the nervous system and musculoskeletal system among patients with PIMs compared with those without PIMs. Besides, polypharmacy users with ACB showed higher rate of prescriptions for the nervous system and the alimentary tract and metabolism system compared with those without ACB. Conclusion: Polypharmacy was significantly associated with negative impact of medication safety among the elderly people in rural area. A persistent remote pharmaceutical care intervention was crucial for improving this problem.